Bacteria-based biopesticides production using shrimp pond sludge as potential cheap culture media and entomotoxicity activity against fruit flies (Bactrocera dorsalis Hendel) - Ulul Azmi, Noormasshela (2015)
Biological controls of destructive pest in forest and agriculture sector using bacteria were proven to minimize the problems caused by the usage of chemical pesticides. However, their application is limited due to high production cost through fermentation. It is therefore necessary to develop potential alternatives culture media for a bacteria-based biopesticides production. In this study, shrimp pond sludge and wastewater were used as an alternate culture media for bacteria-based biopesticides production. The alternate media were prepared under three different preparations; without pre-treatment (unhydrolysed), with acid treatment (hydrolysed) and the supernatant obtained after the centrifugation of the hydrolysed sludge/wastewater. Five species of bacteria been tested for the bacteria-based biopesticides production were Bacillus thuringiensis ATCC33679, Bacillus thuringiensis ATCC10792, Lysinibacillus sphaericus, Klebsiella pneumonia and Aeromonas hydrophillia. The growth rate and sporulation were evaluated throughout the fermentation. Bacillus thuringiensis ATCC 10792 cultured in hydrolysed shrimp pond sludge were selected to be used for the bioassay due to the high growth rate (7.44x107±5.16 CFU/ml) and sporulation (5.90x107±7.88 CFU/ml). Hydrolysed shrimp pond sludge also significantly showed higher growth rate and sporulation compared to unhydrolysed and supernantant. However, variability in the growth rate and sporulation also revealed the preference and requirement of each bacteria to grow and sporulate depends on the species. Further, effectiveness on the usage of alternate culture media was also evaluated on their entomotoxicity level. The bioassay of entomotoxicity test was carried out on the fruit fly larva (Bactrocera dorsalis Hendel) and 81.2% mortality was observed. Larval weight (0.019g ± 0.001) and size (6.97mm ± 0.97) observed on the treated larvae showed significant deterioration compared to the control larvae (with 0.027g ± 0.0003 weight and 10.08mm ± 0.22 in sizes). As well as, the pupation was disrupted in terms of the smaller size of the pupa (30% smaller) and thus, leading to a lower adult fly emergence rate (65.25%). Furthermore, emerged adult fruit fly showed some physical abnormalities on the morphology (undeveloped, crumpled wings and cranked abdomen) and significantly affecting the survival rate of the flies (100% adult flies died after 4 days emerged from the pupa). Since the Bt-based biopesticides have been proven to affect the target insect (B. dorsalis Hendel), toxin produced by the bacteria have been identified. Protein separation conducted by SDS-Page showed the existence of a band with approximately 25 kDa molecular weight. The single band was prepared for protein identification using MALDITOF and three highest protein hits were obtained. The three protein hits identified were superoxide dismutase, spore coat protein and probable transaldolase. Among these three proteins identified, spore coat protein possess direct role in virulence towards the target insect. Therefore, it is strongly believed that this protein is the one that exerted the toxicity activities on the target insect with the presence of Cyt protein. On the whole, this study has proven the potential of Bt ATCC10792 cultured in shrimp pond sludge are able to produce effective biopesticides.